An affinity-matured human monoclonal antibody targeting fusion loop epitope of dengue virus with in vivo therapeutic potency - Tomohiro Kotaki (Nature Portfolio, 2021)
Abstract Dengue virus (DENV), from the genus flavivirus of the family flaviviridae, causes serious health problems globally. Human monoclonal antibodies (HuMAb) can be used to elucidate the mechanisms of neutralization and antibody-dependent enhancement (ADE) of DENV infections, leading to the development of a vaccine or therapeutic antibodies. Here, we generated eight HuMAb clones from an Indonesian patient infected with DENV. These HuMAbs exhibited the typical characteristics of weak neutralizing antibodies including high cross-reactivity with other flaviviruses and targeting of the fusion loop epitope (FLE). However, one of the HuMAbs, 3G9, exhibited strong neutralization (NT50 < 0.1 μg/ml) and possessed a high somatic hyper-mutation rate of the variable region, indicating affinity-maturation. Administration of this antibody significantly prolonged the survival of interferon-α/β/γ receptor knockout C57BL/6 mice after a lethal DENV challenge. Additionally, Fc-modified 3G9 that had lost their in vitro ADE activity showed enhanced therapeutic potency in vivo and competed strongly with an ADE-prone antibody in vitro. Taken together, the affinity-matured FLE-targeting antibody 3G9 exhibits promising features for therapeutic application including a low NT50 value, potential for treatment of various kinds of mosquito-borne flavivirus infection, and suppression of ADE. This study demonstrates the therapeutic potency of affinity-matured FLE-targeting antibodies.